2012
DOI: 10.1371/journal.pone.0036025
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Enzymatically Polymerised Polyphenols on CD4 Binding and Cytokine Production in Murine Splenocytes

Abstract: High-molecular weight polymerised polyphenols have been shown to exhibit anti-influenza virus, anti-HIV, and anti-cancer activities. The purpose of this study was to evaluate the immunomodulating activities of enzymatically polymerised polyphenols, and to clarify the underlying mechanisms of their effects. The cytokine-inducing activity of the enzymatically polymerised polyphenols derived from caffeic acid (CA), ferulic acid (FA), and p-coumaric acid (CoA) was investigated using murine splenocytes. Polymerised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…Because dectin-1 has been reported to synergize with TLR2 or TLR4 [33], these receptors may contribute to the bioactivity associated with the intake of A. brasiliensis fruiting body as food. Furthermore, polymerized substances may also contribute to the immunomodulating activity of this mushroom because of the following reasons: (i) in the present study, we have demonstrated that GM-CSF is a key factor for the induction of cytokine synthesis in murine splenocytes by Agaricus-derived β-glucans, (ii) we have previously reported that A. brasiliensis possesses potent polyphenol oxidase and peroxidase activities in the fruiting body [34][35][36], and (iii) highmolecular-weight polyphenols synthesized by peroxidase induce GM-CSF production in murine leukocytes [37]. GM-CSF exhibits a broad range of biological activities, such as cell differentiation, activation, and inflammatory responses.…”
Section: Discussionmentioning
confidence: 81%
“…Because dectin-1 has been reported to synergize with TLR2 or TLR4 [33], these receptors may contribute to the bioactivity associated with the intake of A. brasiliensis fruiting body as food. Furthermore, polymerized substances may also contribute to the immunomodulating activity of this mushroom because of the following reasons: (i) in the present study, we have demonstrated that GM-CSF is a key factor for the induction of cytokine synthesis in murine splenocytes by Agaricus-derived β-glucans, (ii) we have previously reported that A. brasiliensis possesses potent polyphenol oxidase and peroxidase activities in the fruiting body [34][35][36], and (iii) highmolecular-weight polyphenols synthesized by peroxidase induce GM-CSF production in murine leukocytes [37]. GM-CSF exhibits a broad range of biological activities, such as cell differentiation, activation, and inflammatory responses.…”
Section: Discussionmentioning
confidence: 81%
“…The receptor, which critically modulates the immunoenhancing activity of polymerized polyphenols, remains to be identified. We have previously reported on the interaction between polyphenols and cell surface CD4 [9], also demonstrated that polymerized polyphenols required both T cells and APCs for cytokine synthesis [16]. This suggested that CD4 signal alone could not induce sufficient stimulus to leukocytes.…”
Section: Discussionmentioning
confidence: 97%
“…Polymerized caffeic (pCA), trans-ferulic (pFA) and trans-p-coumaric (pCoA) acids were synthesized as described previously [9]. Briefly, 200 mg of precursor phenylpropanoic acid was neutralized with 1 N NaOH and diluted to 10 mL with phosphate-buffered saline (PBS) containing 1 mg of HRP.…”
Section: Preparation Of Polymerized Polyphenolsmentioning
confidence: 99%
See 2 more Smart Citations